Energy analysis of an air conditioning system using PID and fuzzy logic controllers - Nasution, Henry (2006)
Reducing energy consumption and ensuring thermal comfort are two important considerations in designing an air conditioning system. Alternative approach to reduce energy consumption proposed in this study is to use a variable speed compressor. Two control strategies were proposed, which are proportional plus integral plus derivative (PID) and fuzzy logic controllers. An air conditioning system, originally operates on an On/Off control mechanism, was retrofitted to enable the implementation of the controllers. Measurements and computer interface systems were designed and software to implement the controller algorithms was developed using Visual Basic. The system was installed to a thermal environmental room together with a data acquisition system to monitor the temperature of the room, coefficient of performance, energy consumption and energy saving. Measurements were taken during the two hours experimental period at a time interval of five minutes for temperature setpoints of 20, 22 and 24oC with internal heat loads of 0, 500, 700 and 1000W. Each controller was tuned for the best performance. The results indicate that thermal comfort of the room together with significant energy saving can be obtained through a proper selection of controller parameters. Energy analysis shows that PID and fuzzy logic controllers are better than On/Off control mechanism. Generally, fuzzy logic controller is better than PID controllers. However, conventional controllers such as PID or its combinations are still capable of controlling the space temperature with some amount of energy saving but at the expense of the time to tune the controller parameters. A new PID tuning method based on trial and error was therefore proposed. This study shows that using variable speed compressor and choosing suitable control strategy, the space temperature is able to be controlled with significant energy saving.